Pengaruh Pengaruh kesadaran halal dan sertifikat halal terhadap minat beli produk kentucky fried chicken (KFC) - Ahmad Hamdani; Nurma Sari; Khairil Umuri (Al-Buhuts, 2021)
Halal awareness and halal certification have an important role to prevent consumers from fraudulent forms of a product. This has an impact on consumer buying interest in a product. This study aims to analyze the effect of halal awareness and halal certificates on the interest of KFC consumers in the city of Banda Aceh. Data were collected from 100 questionnaires distributed by KFC consumers in the city of Banda Aceh using purposive sampling technique. Based on data analysis using partial regression and linear regression, the results show that halal awareness has a positive and significant effect on buying interest, while halal certificates have a positive and significant effect on buying interest. So, halal awareness and halal certificate simultaneously have a positive and significant effect on buying interest. Food producers are expected to pay more attention to the halalness of the products they sell, because they can increase consumer buying interest.